2013
DOI: 10.1007/s00442-013-2591-1
|View full text |Cite
|
Sign up to set email alerts
|

Physiological mechanisms drive differing foliar calcium content in ferns and angiosperms

Abstract: Recent evidence points to ferns containing significantly lower contents of foliar calcium and other cations than angiosperms. This is especially true of more ancient 'non-polypod' fern lineages, which predate the diversification of angiosperms. Calcium is an important plant nutrient, the lack of which can potentially slow plant growth and litter decomposition, and alter soil invertebrate communities. The physiological mechanisms limiting foliar calcium (Ca) content in ferns are unknown. While there is a lot we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 75 publications
0
12
1
1
Order By: Relevance
“…Calcium and Mg transport is thus controlled by exchange reactions and depends to a great extent on the flux of cations able to exchange with Ca and Mg (Augusto et al. , Funk and Amatangelo ). Moreover, Ca and Mg uptake in plant roots is mainly a passive process that depends on the mass flow (Marschner ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium and Mg transport is thus controlled by exchange reactions and depends to a great extent on the flux of cations able to exchange with Ca and Mg (Augusto et al. , Funk and Amatangelo ). Moreover, Ca and Mg uptake in plant roots is mainly a passive process that depends on the mass flow (Marschner ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because calcium (Ca) is not easily remobilized from foliage and because actual evapotranspiration drives foliage Ca content (Augusto et al. , Marschner , Funk and Amatangelo , Kumar et al. ), we hypothesize that climate can indirectly influence the Ca remobilization rate.…”
Section: Introductionmentioning
confidence: 99%
“…Ca is also an essential macronutrient (Funk et al, 2013) found in association with the stabilization of the cell wall (White and Broadley, 2003). Plants growing under deficiency of Ca show a reduced number of leaves, early fall of folioles, and dying of the apical bud.…”
Section: Growth Of Seedlingsmentioning
confidence: 99%
“…Calcium is an essential macronutrient for plants [25], playing the important function of cell wall stabilization [26]. In addition, calcium ions and indoleacetic acid influence cell elongation and differentiation [27], and deficiency of this element may retard growth and cause meristem death [22].…”
Section: Biometric Characteristics Assessmentsmentioning
confidence: 99%